2022
DOI: 10.3389/fphy.2022.892215
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Anomalous Forces From a Cooper-Pair Current in High-Tc Superconductors With Nano-Newton Precision

Abstract: Does a supercurrent drag space-time or generate a gravitational field that can be measured in a laboratory environment? A number of theories suggest that space-time itself could be modeled as a superfluid, so a current of Cooper-pairs might couple to its surroundings differently compared to non-quantum matter. On the other hand, experiments appeared in the literature suggesting that a discharge through a high-Tc superconductor generates a force beam, which can be picked up by external sensors. We developed a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…• The gravito-magnetic field, B G , is expelled from a superconductor in a Meissner effect only if there is also a magnetic field satisfying B < − B G (m e /e). This observation is being taken into account for guiding experimental work [101]. The associated penetration depth is found in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• The gravito-magnetic field, B G , is expelled from a superconductor in a Meissner effect only if there is also a magnetic field satisfying B < − B G (m e /e). This observation is being taken into account for guiding experimental work [101]. The associated penetration depth is found in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is found that B G is expelled from the superconductor with a penetration depth on the order of the London penetration depth, provided a magnetic field is also present. This observation is being taken into account for guiding experimental work [101].…”
Section: The Effect Of B On the Penetration Depth Of B Gmentioning
confidence: 99%
“…However, the presence of such 'strange' gravitomagnetic fields would be at odds with known properties of compact objects, such as neutron stars [142]. In addition, a recent work by Tajmar et al [143] imposes narrower constraints on the impact of gravitomagnetic effects on the explanation of anomalous Cooper pair mass excess.…”
Section: Laboratory Testsmentioning
confidence: 99%